TWO FACES OF ENGLISH HEGEMONY IN INDONESIA: AN OVERVIEW - Andini Linarsih; usawinur Barella (Getsempena English Education Journal, 2019)
Mastering English which is currently an international language is one of the golden tickets to explore the world globally. As an educator, having an accredited research journal is an obligation. Nowadays, most international accredited journals are written in English. Therefore, having the ability of English language will help teachers to publish their articles or their writing internationally. Currently, almost all countries in the world prepare their human resources in English language skills. This paper argues that government policies, society, and English language teaching practices are students' environments which promote the emergence of bilingual euphoria phenomenon. Also, this paper will presents how this phenomenon will marginalize local languages together with some suggestions to overcome the situation.